2022
DOI: 10.52289/hej9.108
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic beliefs and written historical reasoning: Exploring their relationship

Abstract: In this descriptive study, we investigated undergraduate students’ epistemic beliefs in history and examined the relationship between students’ beliefs and their performance in written historical reasoning in the context of a historical reasoning course. We measured students’ expressed epistemic beliefs in history through a discipline-specific survey, which we compared with students’ performance when writing a source-based historical argument. A subset of students also participated in a task-based interview to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Basing their analytical framework on Kuhn et al 's model, Ní Cassaithe et al (2022) conducted an interview study with 17 primary school students and found that the students' view on the nature of history and the concept of evidence affect their possibilities for progression in epistemic cognition. Similar results were reported in a survey study with 62 undergraduate students; based on the framework by Stoel et al (2017), Sendur et al (2022) found a strong correlation between epistemic beliefs and the quality of source-based argumentation.…”
Section: Epistemic Cognition and Companion Meaningssupporting
confidence: 85%
See 1 more Smart Citation
“…Basing their analytical framework on Kuhn et al 's model, Ní Cassaithe et al (2022) conducted an interview study with 17 primary school students and found that the students' view on the nature of history and the concept of evidence affect their possibilities for progression in epistemic cognition. Similar results were reported in a survey study with 62 undergraduate students; based on the framework by Stoel et al (2017), Sendur et al (2022) found a strong correlation between epistemic beliefs and the quality of source-based argumentation.…”
Section: Epistemic Cognition and Companion Meaningssupporting
confidence: 85%
“…This is likely to impede the endeavors of history teachers to educate their students so that they can acquire an integrated epistemic cognition of historical knowledge. Such a nuanced epistemic cognition is necessary for developing other relevant aspects of the history subject, such as historical reasoning (Van Boxtel and van Drie, 2017) and source based argumentation (Sendur et al, 2022). Importantly, a more nuanced understanding of historical knowledge also increases individuals' ability to handle conflicting accounts (Nokes, 2014), an ability of great importance for active participation in society (Lee, 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%